Linking cohort data and Welsh routine health records to investigate children at risk of delayed primary vaccination - Lucy Griffiths (Vaccine, 2022)
BackgroundDelayed primary vaccination is one of the strongest predictors of subsequent incomplete immunisation. Identifying children at risk of such delay may enable targeting of interventions, thus decreasing vaccine-preventable illness.ObjectivesTo explore socio-demographic factors associated with delayed receipt of the Diphtheria, Tetanus and Pertussis (DTP) vaccine.MethodsWe included 1,782 children, born between 2000 and 2001, participating in the Millennium Cohort Study (MCS) and resident in Wales, whose parents gave consent for linkage to National Community Child Health Database records at the age seven years contact. We examined child, maternal, family and area characteristics associated with delayed receipt of the first dose of the DTP vaccine.Results98.6% received the first dose of DTP. The majority, 79.6% (n = 1,429) received it on time (between 8 and 12 weeks of age), 14.2% (n = 251) received it early (prior to 8 weeks of age) and 4.8% (n = 79) were delayed (after 12 weeks of age); 1.4% (n = 23) never received it. Delayed primary vaccination was more likely among children with older natural siblings (risk ratio 3.82, 95% confidence interval (1.97, 7.38)), children admitted to special/intensive care (3.15, (1.65, 5.99)), those whose birth weight was > 4Kg (2.02, (1.09, 3.73)) and boys (1.53, (1.01, 2.31)). There was a reduced risk of delayed vaccination with increasing maternal age (0.73, (0.53, 1.00) per 5 year increase) and for babies born to graduate mothers (0.27, (0.08, 0.90)).ConclusionsAlthough the majority of infants were vaccinated in a timely manner, identification of infants at increased risk of early or delayed vaccination will enable targeting of interventions to facilitate timely immunisation. This is to our knowledge the first study exploring individual level socio-demographic factors associated with delayed primary vaccination in the UK and demonstrates the benefits of linking cohort data to routinely-collected child health data.